Efek Iklan Dan Kesadaran Merek Terhadap Citra Merek Serta Implikasinya Pada Loyalitas Pelanggan Followers Instagram Lemonilo - Dita Triana; Winggi Tria Cahya; Sarwoto; Indra Welly Arifin (ITB AAS Indonesia Surakarta, 2025)
This study aims to determine the Effect of Advertising and Brand Awareness on Brand Image and Its Implications on Customer Loyalty of Lemonilo Instagram Followers. The analysis method used in this study is using instrument tests, namely validity and reliability tests. Classic assumption tests, namely normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, determination coefficient analysis (R2), hypothesis tests, namely T tests and Path Analysis. The results of the study indicate that Advertising Affects Lemonilo Brand Image, Brand Awareness Affects Lemonilo Brand Image, Advertising Does Not Affect Lemonilo Customer Loyalty, Brand Awareness Does Not Affect Lemonilo Customer Loyalty, Brand Image Affects Lemonilo Customer Loyalty, Advertising Affects Lemonilo Customer Loyalty With Brand Image as an Intervening Variable, Brand Awareness Affects Lemonilo Customer Loyalty With Brand Image as an Intervening Variable.